(untitled) (Bangladesh Journal of Botany, 2021)
Analgesic, anti-inflammatory and anti-pyretic activities of n-hexane and aqueous ethanolic extracts of Malva neglecta in Swiss albino mice was evaluated. For each activity, the mice were divided into 4 groups: Group 1 served as control, Groups 2 and 3 were given n-hexane and aqueous ethanol extracts, respectively whereas Group 4 was treated with the standard drug. Analgesic activity was evaluated against acetic acid induced writhing, Eddy’s hot plate method, and Formalin induced paw licking. Anti-inflammatory activity was evaluated by carrageenan-induced paw edema. The extracts were also examined for their anti-pyretic activities against yeast-induced pyrexia. Results showed that the n-hexane (p < 0.05) and aqueous ethanolic (p < 0.005) extracts of M. neglecta exhibited analgesic activity by reducing acetic acid-induced writhing, mean reaction time on hot plate model and formalin-induced paw licking in mice as compared to the control. The n-hexane extract (p < 0.05) as well as aqueous ethanolic (p < 0.005) extracts produced significant antiinflammatory activity as compared to the control. Both the n-hexane and aqueous ethanolic extracts revealed significant antipyretic activity (p < 0.005 and p < 0.05, respectively) in mice model. The results of the present study demonstrated that the n-hexane and aqueous ethanol extracts of M. neglecta possess analgesic, antiinflammatory and anti-pyretic activities. Bangladesh J. Bot. 50(3): 577-583, 2021 (September)